The predictive and prognostic significance of cell‐free DNA concentration in melanoma. (28th July 2020) - Váraljai, R.; Elouali, S.; Lueong, S.S.; Wistuba‐Hamprecht, K.; Seremet, T.; Siveke, J.T.; Becker, J.C.; Sucker, A.; Paschen, A.; Horn, P.A.; Neyns, B.; Weide, B.; et al.
Abstract: Background: Melanoma is the leading cause of skin cancer‐related deaths worldwide. While there have been significant improvements in the treatment of advanced melanoma in the past decade, biomarker development lagged behind. Objectives: The majority of liquid biopsy biomarkers rely on the analyses of oncogenic mutations; however, about 20% of melanoma patients are wild type. Therefore, validation of universal predictive and prognostic biomarkers is urgently needed. Methods: We analysed plasma samples in a discovery cohort ( n = 20) and expansion cohort ( n = 166) of metastatic melanoma patients and healthy donors ( n = 116). Total plasma circulating cell‐free DNA (cfDNA) concentrations were measured on the Qubit ® platform using assays for single‐(ss) and double (ds)‐stranded DNA, DNA spectrophotometry and RNase P qPCR. We explored the diagnostic, predictive and prognostic potential of cfDNA concentration by bio‐statistical methods and established a cfDNA threshold for risk stratification. Results: Our selected best method was Qubit ® dsDNA assay which quantified higher plasma cfDNA concentrations in melanoma patients than in healthy controls (AUC 72%). Measurement of baseline cfDNA concentration revealed that high cfDNA was associated with presence of metastases and higher AJCC stage ( P < 0.05). Furthermore, high baseline cfDNA was an indicator of shorter overall survival in patients with oncogenic mutations (HR 2.12, P = 0.0008), and in wild‐type patients (HR 5.55, P < 0.0001). Conclusions: We provide evidence that total cfDNA can be used as a biomarker for melanoma irrespective of the tumour genotype and can provide information on tumour load, risk of progression and risk of death.